(untitled) (Architecture Image Studies, 2026)
Drawing on Bennett’s Developmental Model of Intercultural Sensitivity (DMIS) and Self-Determination Theory (SDT), this study aimed to examine the influences of Sino-Malaysian cooperative education program factors on ICC among undergraduates within a Sino-Malaysian cooperative education program. A quantitative, cross-sectional survey design was employed, using stratified random sampling to recruit 207 students from a population of 982 undergraduates. Data were collected online and analyzed using SPSS and AMOS. The measurement model was validated through confirmatory factor analysis, and structural equation modeling (SEM) was conducted to test the hypothesized relationships. The results indicate that language proficiency (LP) is the strongest predictor of ICC, exerting both direct effects and indirect effects through intrinsic motivation (IM). Intercultural contact (IC) also shows significant dual pathways, enhancing ICC through practical exposure as well as motivational reinforcement. Cultural sensitivity (CS), while exerting a relatively weaker direct effect on ICC, demonstrates its main influence through its capacity to elevate students’ intrinsic motivation. Across all variables, IM emerges as a consistent partial mediator, highlighting the importance of motivational processes in the development of ICC. These findings underscore the need to integrate language development, cultural awareness, and authentic intercultural experiences into program design. The study’s cross-sectional nature, reliance on self-reported data, and sampling from a single institution suggest that future research should adopt longitudinal designs and examine more diverse student populations to strengthen generalizability.